Hyporheic hot moments: Dissolved oxygen dynamics in the hyporheic zone in response to surface flow perturbations. Issue 8 (7th August 2017) - Kaufman, Matthew H.; Cardenas, M. Bayani; Buttles, Jim; Kessler, Adam J.; Cook, Perran L. M.
Abstract: Dissolved oxygen (DO) is a key environmental variable that drives and feeds back with numerous processes. In the aquatic sediment that makes up the hyporheic zone, DO may exhibit pronounced spatial gradients and complex patterns which control the distribution of a series of redox processes. Yet, little is known regarding the dynamics of hyporheic zone DO, especially under transitional flow regimes. Considering the natural tendency of rivers to be highly responsive to external forcing, these temporal dynamics are potentially just as important and pronounced as the spatial gradients. Here we use laboratory flume experiments and multiphysics flow and reactive transport modeling to investigate surface flow controls on the depth of oxygen penetration in the bed as well as the area of oxygenated sediment. We show that the hyporheic zone DO conditions respond over time scales of hours‐to‐days when subjected to practically instantaneous surface flow perturbations. Additionally, the flume experiments demonstrate that hyporheic zone DO conditions respond faster to surface flow acceleration than to deceleration. Finally, we found that the morphology of the dissolved oxygen plume front depends on surface flow acceleration or deceleration. This study thus shows that the highly dynamic nature of typical streams and rivers drives equally dynamic redox conditions in the hyporheic zone. Because the redox conditions and their distribution within the hyporheic zone are important from biological, ecological, and contaminant perspectives, this hyporheic redox dynamism has the potential to impact system scale aquatic chemical cycles. Plain Language Summary: The amount of dissolved oxygen (DO) in water is important both in rivers and their underlying sediment. River discharge is constantly changing, and since it is the river's flow which drives flow in the bed, the pronounced chemical and biological gradients within the riverbed may also be constantly changing. We used laboratory experiments and computational models to explore how fast the DO in the bed changes in response to changes in the river velocity. We found that small changes in river velocity created large changes in riverbed DO conditions. We also found that the riverbed DO conditions changed much slower than the river velocity, and that the riverbed response was faster when the river velocity increased and slower when the river decelerated. The shape of the high DO area in the riverbed depended on whether the river water was speeding up, slowing down, or steady. We observed short‐lived areas of low DO in what were mostly high DO zones, and vice versa, particularly when the river water was decelerating. This study thus showed that the riverbed is highly dynamic, subject to large changes in DO that can last much longer than the variations in the river flows that cause them. Key Points: Experiments and models show that changes in channel water velocity lead to significant dynamic response in hyporheic zone dissolved oxygen The hyporheic zone response time scale is much longer than the open channel perturbation time scale Hyporheic response time scales and dissolved oxygen plume morphology exhibit hysteresis relative to channel velocity change